Molecular Cloning And Functional Characterization Of A Novel Elovl (Elongase) Family From A Freshwater Teleost (Oreochromis Niloticus) - Han, Wan Yin (2017)
At present, seven members of ELOVL family (ELOVL1-7) have been identified in mammals. In terms of function, they are broadly divided into those that elongate the saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA), and those that elongate the polyunsaturated fatty acids (PUFA). Recently, a group of Elovl proteins, termed as Elovl4-like, was discovered from teleost. However, these proteins have shown low identities and different in term of function with the typical identified Elovl4 protein. An interest has arisen to investigate whether this group of Elovl proteins could be a new Elovl family member or as a subfamily of the existing Elovl member.